Modulation of Gamma and Alpha Activity during a Working Memory Task Engaging the Dorsal or Ventral Stream - Jokisch, Daniel; Jensen, Ole (The Journal of neuroscience, 2007)
Despite extensive experimental work in both animals and humans, the actual role of oscillatory brain activity for working memory maintenance remains elusive. Gamma band activity (30–100 Hz) has been hypothesized to reflect either the maintenance of neuronal representations or changing demands in attention. Regarding posterior alpha activity (8–13 Hz), it is under debate whether it reflects functional inhibition or neuronal processing required for the task. The aim of the present study was to further elucidate the role of oscillatory brain activity in humans using a working memory task engaging either the dorsal or ventral visual stream. We recorded brain activity using magnetoencephalography from subjects performing a delayed-match-to-sample task. Subjects were instructed to remember either the identity or the spatial orientation of shortly presented faces. The analysis revealed stronger alpha power around the parieto-occipital sulcus during retention of face identities (ventral stream) compared with the retention of face orientations (dorsal stream). In contrast, successful retention of face orientations was associated with an increase in gamma power in the occipital lobe relative to the face identity condition. We propose that gamma activity reflects the actual neuronal maintenance of visual representations, whereas the alpha increase is a result of functional inhibition.